(untitled) (Journal of actual problems of jurisprudence, 2023)
The intensive development of information and digital technologies in the implementation of the needs of civil turnover has necessitated the introduction of appropriate payments and money transfers using information and communication technologies. The appearance in recent decades of one of the instruments of conducting - "electronic money" — has led to the emergence of significant practical and scientific interest. Moreover, the variety of electronic money in various states and in the global financial system has increased dramatically. The purpose of the work is to study questions about the development of the history and prospects of the development of electronic money and electronic payments in the world and to analyze the development of this institution in Kazakhstan. A systematic analysis of the currently used methods of electronic payments of non-cash monetary transactions allowed the author to substantiate the position of different approaches and in some issues common approaches in different countries. By means of a formal legal and comparative legal analysis of doctrinal positions, legal definitions of electronic payments and electronic money in the legislation of Kazakhstan, the United States, Great Britain, Singapore, China, signs of electronic money that distinguish them from other means of electronic payments have been identified. As a result of the analysis of the ratio of such objects of civil rights as money and cash, it is summarized that electronic money should be attributed to non-cash funds in electronic form. Keywords: electronic money, cashless payment, electronic payment systems, security of payment systems, money.